Nkanelo wa mirhi yo hambana ya xifundzantsongo xa Bush-Buckridge eka vutshunguri bya mavabyi - Serepe, R. S. (My University, 2013)
It appears that nowadays in life every human being believe in medication given from hospitals meanwhile all diseases can be cured by healing trees that we discovered in Bushbuckridge region To achieve the aim of this proposal we will use an interview method, content analysis, textual analysis together with an unstructured interview. These methods will also be supported by an open-ended questionnaires whereby anyone can be questioned to give their point of view about healing trees. The study will review to people that not only the doctor`s medicine is able to heal the diseases but the study of healing trees and research can also come to rescue.
The importance of different trees in the Bushbuckridge region in the treatment of diseases
Thesis (M.A. (African Languages)) -- University of Limpopo, 2013
Keywords: Healing trees; Diseases; Medicine; Trees; Tsonga (African people); Medicinal plants